STUDI KOMPARATIF PENERAPAN ETIKA PROFESI DALAM AKUNTANSI DI INDONESIA DAN INTERNASIONAL - Liana Oly Kisanto; Muhammad Dafa Syahrulli; Evaristo Panesa Lonsong; Oswaldus Antonius Karo; Rizki Putra Pratama (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
In the era of globalization, the accounting profession is required to maintain integrity and accountability amid the complexity of different economic systems and cultures. Although international ethical standards have been harmonized, their application in countries like Indonesia still faces local challenges. This research aims to conduct a comparative study of the application of accounting professional ethics between Indonesian and international accountants, in order to gain a deeper understanding of the similarities, and differences in their implementation. The research method used is descriptive comparative with a qualitative approach. The results showed that both Indonesian and international standards apply similar principles of accounting professional ethics, such as integrity, objectivity, competence, confidentiality, and professional behavior, and are supported by a systematic conceptual framework. The difference lies in the institutional structure, depth of regulation, and scope of implementation, but both still lead to global harmonization to maintain integrity and public trust in the accounting profession.